The impacts of natural disasters on power systems: Anatomy of the marmara earthquake blackout - (:unkn) unknown (My University, 2010)
An earthquake is an instantly occurring and unpredictable natural event. The potential and effects of earthquakes and other natural disasters on power systems are system faults. The faults are not only limited to the physical damage of power systems, but power quality disturbances may also take place. The Marmara Earthquake, which occurred in Turkey on Aug 17, 1999, caused death and catastrophe. After the earthquake, the Turkish Power System collapsed. This is the largest power blackout in Turkey in last twenty years. In this study, the impact of the Marmara earthquake on the Turkish power system are described and the Marmara Earthquake Blackout is examined in detail as regards the qualitative behavior of the power system.
Keywords: Overvoltages in power systems; Power system blackouts; Power system disturbances